Legal Responsibility for Patient Rights for Negligence in Health Services According to Law Number 44 of 2009: Tanggung Jawab Hukum Terhadap Hak-Hak Pasien Atas Kelalaian Dalam Pelayanan Kesehatan Menurut Undang-Undang Nomor 44 Tahun 2009 - Amalia, Cindy Ratna (Prosiding University Research Colloquium, 2024)
Hospitals are health care institutions that organize comprehensive individual health services that provide inpatient, outpatient, and emergency care. Based on Article 46 of Law Number 44 of 2009 concerning Hospitals, which states that hospitals are legally responsible for all losses caused by the negligence of health workers in hospitals. As the law develops, the position of patients as consumers and doctors and other medical personnel as health servants becomes equal. This equal position then creates rights and obligations that must be fulfilled from each party. This study aims to determine the responsibility of hospitals for the negligence of their medical personnel and the legal protection of patients in the act of childbirth performed in hospitals by being linked to Law Number 36 of 2009 concerning Health. This research is made using normative juridical methods through legal and conceptual approaches with primary, secondary and tertiary legal materials to support the research. The result of this research is legal certainty related to the hospital’s responsibility towards the patient and legal protection of the patient’s rights for negligence committed by medical personnel.